2015
DOI: 10.1007/s11060-015-1789-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumor bed radiosurgery: an emerging treatment for brain metastases

Abstract: While typically used for treating small intact brain metastases, an increasing body of literature examining tumor bed directed stereotactic radiosurgery (SRS) is emerging. There are now over 1000 published cases treated with this approach, and the first prospective trial was recently published. The ideal sequencing of tumor bed SRS is unclear. Current approaches include, a neoadjuvant treatment before resection, alone as an adjuvant after resection, and following surgery combined with whole brain radiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Several retrospective [42][43][44] and one prospective phase II trial 45 reported local control rates at 1 year around 80% (70%-90%) and a median survival of 10-17 months (class IIIa): this suggests that postoperative SRS is as effective as WBRT in achieving local control. An alternative approach is the use of SFRT, presumed to be associated with lower risk of radionecrosis in larger lesions.…”
Section: Stereotactic Radiosurgery/stereotactic Fractionated Radiothementioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective [42][43][44] and one prospective phase II trial 45 reported local control rates at 1 year around 80% (70%-90%) and a median survival of 10-17 months (class IIIa): this suggests that postoperative SRS is as effective as WBRT in achieving local control. An alternative approach is the use of SFRT, presumed to be associated with lower risk of radionecrosis in larger lesions.…”
Section: Stereotactic Radiosurgery/stereotactic Fractionated Radiothementioning
confidence: 99%
“…An alternative approach is the use of SFRT, presumed to be associated with lower risk of radionecrosis in larger lesions. 44,46 The balance between risk and benefit is currently unknown with unsolved issues, such as the optimal dose and fractionation and the effects on survival, quality of life, and cognitive function. Randomized trials are ongoing.…”
Section: Stereotactic Radiosurgery/stereotactic Fractionated Radiothementioning
confidence: 99%
“…Furthermore, the study also established that brain metastasis patients who received intraoperative permanent Cs-131 brachytherapy implants experienced an improvement in their self-assessment of quality of life and neurocognitive status [ 64 ]. Furthermore, besides having excellent local control of metastasis, the study also found that an intraoperative permanent Cs-131 brachytherapy implant is likely to improve brain tumor patients' quality of life and cognitive function [ 65 ].…”
Section: Reviewmentioning
confidence: 99%
“…For postoperative irradiated cavities with single-fraction SRS or fSRT, Minniti et al found 12 months estimated risk rates between 1.5 % and 28 %, respectively, with no observable clinical or treatment differences in the two groups [56] . Since no major differences were observed and fractionated treatment regimens are more commonly used for larger treatment volumes, fSRT seems to be a favorable treatment modality, particularly for larger target volumes [22] , [23] , [56] . However, additional evidence is needed including prospectively evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…With an increasing treatment volume, the threshold to develop radiation-induced contrast enhancements (RICE) and clinically evident radiation necrosis (RN) [20] and the effectiveness in relation to the LC [21] decline. Fractionated stereotactic radiotherapy (fSRT) is an alternative treatment approach to SRS [22] , [23] . On the one hand, with fractionated dose schedules the risk of RICE can be reduced, especially in larger cavities [24] , [25] .…”
Section: Introductionmentioning
confidence: 99%